Adaptive facade: aluminium solar shading design - Zulkepli, Nor Rasyidah (2022)
Construction technologies are progressing quickly, according to the Construction Association, with 29 percent of businesses investing in technology to increase worker responsibilities. These investments in innovation pay off handsomely; according to the US Chamber of Commerce, 70 percent of contractors believe that contemporary technology improves productivity, schedules, and safety. For many years, our industry has been lacking in innovation. Construction has fallen substantially behind other industries, such as autos, in adapting to the digital age. Our industry lacks innovation since it requires substantial research, lacks standardisation, material supply may be challenging, and there is a skilled worker shortage. Furthermore, the fragmentation and lack of coordination across the many segments of the building value chain make it difficult for commercial innovation to arise. Innovation is critical, particularly in the educational context. The majority of educational environments are still designed with little deviation from the classical industrial model, particularly when it comes to student housing. This campus of the twenty-first century should not only provide an innovative synthesis of space and technology, but it should also provide a new instructional approach. The government has recently begun to change and adopt the green campus concept in order to improve the educational environment for students. A green campus performs these activities in accordance with a system-wide culture of environmental sustainability, balancing function and design with available and anticipated resources. A green campus is one in which ecologically responsible practise and education coexist, and where environmental principles are demonstrated by example. According to this research assessment, student housing should include a variety of goals and approaches, as well as novel methods combined with standard triangulation methods. In order to increase knowledge sharing in the area, researchers in the learning space should strive for detailed documentation and wider distribution of their findings. In order to fulfil green campus and sustainable design goals, four innovations can be utilised.